Stars behind bars. I. The Milky Way's central stellar populations - Buck, Tobias (The astrophysical journal, 2018)
We show for the first time that a fully cosmological hydrodynamical simulation can reproduce key properties of the innermost region of the Milky Way (MW). Our high-resolution simulation reproduces qualitatively the profile and kinematics of the MW’s boxy/peanut-shaped bulge, and hence we can use it to reconstruct and understand the bulge assembly. In particular, the age dependence of the X-shape morphology of the simulated bulge parallels the observed metallicity-dependent split in the red clump stars of the inner Galaxy. We use this feature to propose an observational metric that (after calibrated against a larger set of simulations) might allow us to quantify when the bulge formed from the disk. The metric we propose can be employed with upcoming survey data to constrain the age of the MW bar. From the split in stellar counts we estimate the formation of the 4 kpc scale bar in the simulation to have happened Gyr ago, in good agreement with conventional methods to measure bar formation in simulations. We test the prospects for observationally differentiating the stars that belong to the bulge/bar compared to the surrounding disk, and we find that the inner disk and bulge are practically indistinguishable in both chemistry and ages.